Escalonius, a new subgenus of Calochromus Guérin-Méneville, 1833 identified by the molecular phylogeny of Calochromini (Coleoptera: Lycidae) - Motyka, Michal; Bocak, Ladislav (Zootaxa, 2018)
Calochromini is a net-winged beetle lineage with seven genera and world-wide distribution. The recently collected morphologically divergent Calochromus amabilis Lea, 1899 was sequenced to recover its relationships and a three-marker DNA dataset was assembled from 27 Calochromini from GenBank and new data for C. amabilis. The phylogenetic analysis recovered C. amabilis nested deep within Calochromus s. l. in a sister-position to Calochromus s. str. C. amabilis represents an early diversified and morphologically distinct species, for which the subgenus Escalonius subgen. nov. is erected. In contrast with its phylogenetic relationships, Escalonius subgen. nov. differs from other morphologically uniform Calochromus subgenera. Calochromus (Escalonius) amabilis has a small body, serrate antennae, the pronotum with concave lateral margins, and the long phallus surpassing the apices of parameres. The results demonstrate the unlinked morphological and molecular evolution of Calochromini.         The key to world genera and subgenera is presented and all diagnostic characters are illustrated.